Capsular polysaccharide types of group B streptococcal isolates from neonates with early-onset systemic infection - Lin, F Y; Clemens, J D; Azimi, P H; Regan, J A; Weisman, L E; Philips, 3rd, J B; Rhoads, G G; Clark, P; Brenner, R A; Ferrieri, P (The Journal of infectious diseases, 1998)
The distribution of serotypes of group B streptococci (GBS) isolated from 67 infants with early-onset sepsis are described. Case-infants were assembled from 13 hospitals across the United States from 15 July 1995 to 5 February 1997 through prospective active surveillance. The distribution of GBS serotypes was Ia, 40%; Ib, 9%; II, 6%; III, 27%; V, 15%; and nontypeable, 3%. Type V occurred more frequently in the northeast region (New York and New Jersey) than in other regions (29% vs. 9%, P = .06). Conversely, type III occurred significantly less frequently in the northeast region than other regions (10% vs. 35%, P = .04). GBS types Ia, III, and V accounted for 82% of the isolates. This report supports previous observations about the emergence of GBS type V, but our data caution that conclusions about serotype distributions based on one geographic location or on a small number of patients may not be generally applicable. Continued monitoring seems necessary for the design of a GBS vaccine.